The routine of relative /companion to the child with cancer during hospitalization - Raquel dos Anjos Silveira; Isabel Cristina dos Santos Oliveira (Rev Rene)
The study has as objectives to describe the relatives/companions’ bio-psychosocial needs and analyze the relatives /companions’ routine concerning children with oncological disease. It was made a qualitative research with seven relatives/companions of these children, and it was used a form for the relatives’ characterization and it was made a non-directive interview in groups. The oncological disease alters significantly the daily life of the child family/companion with regard to the bio-psychosocial needs. The family strengthens the familiar ties in difficult moments, like the ones of risk to the child’s integrity, and also establishes support that transposes the institutional wall and expands it to the community. Taking into account the reports, it considered relevant the development of new studies directed to the family as focus of attention.